Towards international collaboration of clinical research networks for EMDR: the EMDR Pain Network Germany - Vock, S.; Hofmann, A.; Lehnung, M.; Böhm, K.; Wieland, S.; Seidler, G. H.; Beiner, E.; Hermes, M.; Friederich, H.-C.; Eich, W.; Tesarz, J. (Frontiers in Psychology, 2024)
Background Eye Movement Desensitization and Reprocessing (EMDR) is an evidence-based treatment, primarily established for post-traumatic stress disorder (PTSD). While it is increasingly being applied to chronic pain, its efficacy in this area is not yet supported by the same level of evidence as that which exists for PTSD. Studies in this area often show heterogeneous results with small case numbers, and the potential side effects of EMDR in the treatment of chronic pain are not well understood. Systematic documentation of treatment effects, potential predictors of treatment response and non-response, and side effects is crucial for progress in this field. Aim The primary aim is to establish a research framework to systematically investigate the delivery of EMDR therapies by outpatient clinicians in the field of pain. This study aims to provide a comprehensive analysis of treatment outcomes, side effects and determinants of treatment effectiveness, whether positive response or non-response. Methods This framework will oversee the documentation and evaluation of EMDR interventions delivered in outpatient settings using an Embedded Continuous Cumulative Evaluation Design (ECCED). It will focus on detailed characterisation of positive and negative therapeutic effects. It will also identify and analyse prognostic factors that influence individual variability in response to treatment. Treatment materials, standardised assessments and an intervision platform for regular exchange will be provided. Discussion The establishment of the EMDR Pain Network Germany and an interdisciplinary scientific-clinical platform is essential to promote clinical exchange and understanding of the effects of EMDR in pain therapy. This platform offers standardised treatment protocols, an online data collection system with anonymised data, comprehensive baseline assessments and an intervision platform for regular exchange. The knowledge gained is intended to personalise future therapies and serve as a basis for large randomised clinical trials.